Towards the Greater Good? EU Commissioners' Nationality and Budget Allocation in the European Union - Kai Gehring; Stephan A. Schneider (University of Heidelberg, Department of Economics, 2015)
We analyse whether there is a relationship between EU Commissioners' national origin and political outcomes. For this purpose, we argue that examining the Commissioner for Agriculture allows the most precise empirical identification: there is a specific budget for agriculture which accounts for the largest share of the overall EU budget and gives significant leeway to the Commissioner. On average, providing the Commissioners is associated with increases in the share of the overall EU budget that is allocated to their country of origin of about one percentage point. This increase corresponds to half a billion Euro per year, a significant change in particular for smaller member states. Alternative explanations are considered using country-specific time trends, examining pre- and post-treatment trends and modeling endogenous treatment-selection. There are no significant differences in trend behavior between treated and non-treated countries both before and after providing the Commissioner. We demonstrate that our results are not driven by individual countries and show that selection-on-unobservables would have to be implausibly high to account for the estimated coefficient.
urn:nbn:de:bsz:16-heidok-189373
Keywords: 330; Fiscal Federalism; Political Economy; Budget Allocation; European Union; EU Commission; EU Commissioners; National Origin